Fe–N4 engineering of S and N co-doped hierarchical porous carbon-based electrocatalysts for enhanced oxygen reduction in Zn–air batteries. Issue 42 (15th October 2020) - Gao, Jingxia; Liu, Sa; Zhu, Ping; Zhao, Xinsheng; Wang, Guoxiang
Abstract : A highly active yet stable electrocatalyst was prepared by in situ formed template-assisting method. Abstract : The development of high-performance non-noble metal cathode catalysts is a cutting-edge approach for efficient energy conversion and storage devices. Here, we describe an in situ -formed template-assisted method to prepare a highly active yet stable electrocatalyst (FeSN-HPC) that possesses abundant Fe–N4 sites uniformly dispersed in S and N co-doped hierarchical porous carbon. Compared to commercial Pt/C in alkaline electrolyte, the sample FeSN-HPC displays superior and enhanced oxygen reduction reaction (ORR) activity (0.86 V of half-wave potential) and stability (only 14 mV degradation of half-wave potential after durability tests). The high electrocatalytic activity of FeSN-HPC mainly originates from the synergistic effect of efficient N dopants (such as pyridinic N, graphitic N, and Fe II –N4 ) and the desirable hierarchical porous architecture. Expectedly, the primary Zn–air battery (ZAB) with FeSN-HPC as the cathode electrocatalyst exhibits an outstanding discharge performance, with a maximal power density of 200 mW cm −2 . Additionally, the sample FeSN-HPC also has promising potential for application in solid and flexible ZABs.